2013
DOI: 10.1063/1.4821810
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence of the modulation of a plane wave to oblique perturbations and generation of rogue waves in finite water depth

Abstract: We present a laboratory experiment in a large directional wave basin to discuss the instability of a plane wave to oblique side band perturbations in finite water depth. Experimental observations, with the support of numerical simulations, confirm that a carrier wave becomes modulationally unstable even for relative water depths k0h < 1.36 (with k the wavenumber of the plane wave and h the water depth), when it is perturbed by appropriate oblique disturbances. Results corroborate that the underlying mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 38 publications
(49 reference statements)
2
34
0
Order By: Relevance
“…Such results have been confirmed through recent numerical simulations of the Euler equations and experimental work performed in the MARINTEK Laboratories (Toffoli et al, 2011). The investigations have showed that the kurtosis, a measure of the probability of occurrence of extreme waves, depends on an angle β between the crossing wave systems.…”
Section: Hindcast Datasupporting
confidence: 61%
See 2 more Smart Citations
“…Such results have been confirmed through recent numerical simulations of the Euler equations and experimental work performed in the MARINTEK Laboratories (Toffoli et al, 2011). The investigations have showed that the kurtosis, a measure of the probability of occurrence of extreme waves, depends on an angle β between the crossing wave systems.…”
Section: Hindcast Datasupporting
confidence: 61%
“…The recognized mechanisms responsible for the occurrence of rogue waves can be classified as follows (Onorato et al, 2006a(Onorato et al, , b, 2010Toffoli et al, 2011;Didenkulova, 2010;Didenkulov and Pelinovsky, 2011;Sergeeva et al, 2011Sergeeva et al, , 2013: -shallow water effects.…”
Section: Hindcast Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Under the influence of unstable side bands, however, modulational instability survives beyond this critical water depth and a significant amplification can be achieved also for relatively shallow water with k 0 h < 1.36, provided the perturbations are properly selected within the instability region. This is also in agreement with other experimental and numerical studies (Yuen and Lake, 1982;Trulsen and Dysthe, 1996;Trulsen et al, 1999;Tulin and Waseda, 1999;Gramstad and Trulsen, 2011;Toffoli et al, 2013). For relative water depth k 0 h = 0.8, simulations did not indicate any significant growing of the modulations, though.…”
Section: Discussionsupporting
confidence: 81%
“…It is important to mention that the timescales are consistent with the generation of rogue waves in the laboratory (see, in this regard, a recent comparison between experimental data and HOSM simulations in Toffoli et al, 2013).…”
Section: Temporal Evolution Of Wave Amplitudementioning
confidence: 99%